Notes on Multiperiod Valuation and the Pricing of Options - BHATTACHARYA, SUDIPTO (Journal of Finance, 1981)
ABSTRACT A mean‐variance risk‐return tradeoff relationship is derived for the diffusion process limiting case of a state‐preference model, with aggregate consumption serving as a pivotal variable. The model is compared to other recent models along the dimensions of generality and tractable implementation. The incorporation of stochastic interest rates in general equilibrium and arbitrage‐based valuation models is examined, and an extension to earlier methods is discussed, in connection with the implementation of “robust” general valuation procedures.